2019
DOI: 10.3390/ijfs7010006
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Investigation of the Performance of Japanese Mutual Funds: Skill or Luck?

Abstract: This paper assesses the performance of 355 actively managed Japanese Equity Mutual Funds between April 2011 and April 2016. The equal weight portfolio and Jensen’s alpha measures of active management provide strong evidence that Japanese Mutual Funds fail to outperform the benchmark four-factor capital asset pricing model. When it comes to market timing, the Treynor and Mazuy measure shows that 33 funds have significant positive market timing ability which is largely offset by 31 funds with significant negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Therefore, the funds that make the greatest number of important errors in the past are also those that make the greatest number of important errors in the future that is not contradictory with global learning in which all funds generally have fewer important errors over time, and is based on the result associated to the coefficient for the time variable (Time t ). This result is consistent with Pilbeam and Preston (2019) who show persistence in the relative skill of mutual funds. These authors document that the lowest-performing funds in one period are still the worst-performing funds in the following period.…”
Section: Learning In the Mutual Fund Industrysupporting
confidence: 92%
“…Therefore, the funds that make the greatest number of important errors in the past are also those that make the greatest number of important errors in the future that is not contradictory with global learning in which all funds generally have fewer important errors over time, and is based on the result associated to the coefficient for the time variable (Time t ). This result is consistent with Pilbeam and Preston (2019) who show persistence in the relative skill of mutual funds. These authors document that the lowest-performing funds in one period are still the worst-performing funds in the following period.…”
Section: Learning In the Mutual Fund Industrysupporting
confidence: 92%
“…The absolute superior returns are lower for multifactor models. Pilbeam and Preston (2019) studied the performance of 355 actively managed Japanese Mutual Funds between 2011 and 2016. Using Jensen's alpha measures, the authors found that the Japanese Mutual Funds underperformed the benchmark.…”
Section: Active Management Strategiesmentioning
confidence: 99%
“…They also discovered that the distribution of fund alphas was consistent with a mixture of skill and luck but with a greater emphasis on luck. However, Pilbeam and Preston (2019) suggested that while a small number of funds exhibit skill, most funds do not appear to possess skill, and their performance can be attributed to luck. The authors further explained that the predictability of fund performance is weak, indicating that historical performance is not a reliable predictor of future performance.…”
Section: Mutual Fund Performance and Managers' Skillsmentioning
confidence: 99%